Nitro-fatty acid pharmacokinetics in the adipose tissue compartment - Fazzari, Marco (J Lipid Res, 2017)
Electrophilic nitro-FAs (NO(2)-FAs) promote adaptive and anti-inflammatory cell signaling responses as a result of an electrophilic character that supports posttranslational protein modifications. A unique pharmacokinetic profile is expected for NO(2)-FAs because of an ability to undergo reversible reactions including Michael addition with cysteine-containing proteins and esterification into complex lipids. Herein, we report via quantitative whole-body autoradiography analysis of rats gavaged with radiolabeled 10-nitro-[(14)C]oleic acid, preferential accumulation in adipose tissue over 2 weeks. To better define the metabolism and incorporation of NO(2)-FAs and their metabolites in adipose tissue lipids, adipocyte cultures were supplemented with 10-nitro-oleic acid (10-NO(2)-OA), nitro-stearic acid, nitro-conjugated linoleic acid, and nitro-linolenic acid. Then, quantitative HPLC-MS/MS analysis was performed on adipocyte neutral and polar lipid fractions, both before and after acid hydrolysis of esterified FAs. NO(2)-FAs preferentially incorporated in monoacyl- and diacylglycerides, while reduced metabolites were highly enriched in triacylglycerides. This differential distribution profile was confirmed in vivo in the adipose tissue of NO(2)-OA-treated mice. This pattern of NO(2)-FA deposition lends new insight into the unique pharmacokinetics and pharmacologic actions that could be expected for this chemically-reactive class of endogenous signaling mediators and synthetic drug candidates.